Silenced Voices on the Net: A Systematic Literature Review on Gender-Based in Social Media Networks - Duche-Pérez, Aleixandre Brian; Grundy-López, Ricardo Enrique; Gutierrez-Aguilar, Olger; Vera-Revilla, Cintya Yadira; Romero, Ángela Valeria Mya Pazo (Journal of Ecohumanism, 2024)
Gender-based violence against women on social media networks is a significant problem due to its pervasive and harmful impact on individuals and society as a whole. This issue manifests in various forms, including harassment, threats, and abuse, which can have severe psychological, emotional, and physical consequences for the victims. This systematic review identifies and analyzes the dynamics of gender-based violence on digital platforms, particularly during the COVID-19 pandemic, using a systematic methodology according to PRISMA guidelines. The findings reveal that while social media can be powerful tools for empowerment and connection, they also perpetuate and facilitate forms of violence that reflect and amplify the inequalities and abuses of the physical world. The study concludes that it is imperative to recognize and address these dynamics to protect and empower women in all spaces, both physical and digital.